Fundamentals of Entrepreneurship (ENT300) : Food truck / Angela Bakil … [et al.] - Bakil, Angela; Jesikel, Isabel Kimbly; Mambang, Evelyn (2017)
Food truck is about to selling a various menu of foods; basically lunch meals to different category of clients on the go to. The aim of setting up Food Truck is to take our various types of meals and soft drink such as chapman, punch, non-alcoholic wines, smoothies and fresh fruit juice. This business is a partnership form. Our restaurant is located at Sublot 40, Ground Floor, Block B, Stutong Parade Commercial Centre, Jalan Setia Raja, 93350, Kuching Sarawak.